Ethical Issues in Disaster Management - Kubilay Kaptan (Doğal Afetler ve Çevre Dergisi)
The predictions related to earthquakes have drawn the attention of society as well as media in the developing countries where the ‘common’ people have different perceptions. Most often, popular myths take over scientific facts among the public, and this can lead to rumors about natural hazards. This article will mention rumors related to natural disasters, and particularly the rumors regarding the response of society, media and government when earthquakes happen. This research emphasizes the ethical responsibility needed to be undertaken by scientists to avoid panic instead of the rumors by pseudo-experts. This article summarizes the efforts provided by the scientists to prevent the recent rumors about a sudden water rise in Lake Van, the flash flood occurred in the Samsun Province and the earthquake happened (M 6.7, October 23, 2011) in the Van Province in Turkey.